STUDENTS’ STRATEGIES USING DIGITAL TECHNOLOGY TO SUPPORT SELF-REGULATED LEARNING IN LEARNING CALCULUS 1 - Ni Kadek Ayu Indah Mahandari; Deshinta Puspa Ayu Dwi Argaswari (HISTOGRAM: Jurnal Pendidikan Matematika, 2023)
This study aims to explain how Sampoerna University students use digital technologies to self-regulate their learning strategy in learning Calculus 1 during online learning. This study uses descriptive qualitative. The population are students of Sampoerna University who took Calculus 1 during online learning. This study use Yot-Dominguez and Marcelo instrument, and Zimmerman SRL Model to analyse students’ self-regulated learning strategy using digital technology. The result shows the students utilize communication tools for seeking the social support through instant messaging like WhatsApp and digital conferencing tools such as Zoom, Google Meet, and Microsoft Teams. Then, the students utilize other technology to organize and transform through online scientific calculator such us Symbol Lab, Geogebra, Desmos Calculator, Algebra and Trigonometry Calculator, and digital scanner (Cam Scanner and Office Lens). Furthermore, they tend to searching for information on the repository tools such as Canvas, Youtube, Instagram, TikTok and Blogs. Moreover, the students use assessment tools to verify their understanding through Youtube, Khan Academy and Paul’s Notes. Other than the digital technologies mentioned above, students also utilize several digital technologies in occasional use.